Translational Control in Sea Urchin Eggs and Embryos: Initiation is Rate Limiting in Blastula Stage Embryos - Hille, M. B. (1981)
To determine whether initiation is rate-limiting in protein synthesis during the embryogenesis of sea urchins, polyribosome profiles of unfertilized eggs and cleavage, blastula and prism stage embryos were examined after incubation of the eggs and embryos in the presence and absence of low amounts of emetine, an inhibitor of polypeptide elongation. The ribosomes were radioactively labeled with [(3)H]uridine by injection of the adults during oogenesis so that we could monitor emetine-dependent shifts of monoribosomes to polyribosomes. Although initiation is not rate limiting in unfertilized eggs or 2- to 16-cell embryos of Strongylocentrotus purpuratus, it is rate limiting in blastula and prism embryos. We suggest that initiation becomes rate limiting to allow the selective translation of certain classes of mRNA during later development.